Biomorphic carbon derived from corn husk as a promising anode materials for potassium ion battery. (20th November 2019) - Wang, Qing; Gao, Chenglin; Zhang, Wanxing; Luo, Shaohua; Zhou, Meng; Liu, Yanguo; Liu, Ronghui; Zhang, Yahui; Wang, Zhiyuan; Hao, Aimin
Abstract: In this study, biomorphic hard carbon is prepared from corn husk using the one-step carbonization method and used as a potassium-ion battery anode material. The biocarbon anode with extremely small specific surface area (3.4 m 2 g −1 ) demonstrates better electrochemical performance than those with large specific surface areas. Particularly, at a current density of 0.1 A g −1, the carbon electrode delivers first discharge and charge capacities of 396.2 and 231.0 mAh g −1, respectively. After 100 cycles, the reversible capacity retention rate is 89.1%. Moreover, at a high current density of 1 A g −1, the reversible capacity reaches approximately 135.3 mAh g −1 after 500 cycles. This excellent performance is attributed to the enhancement of ion diffusion kinetics because of the hierarchically porous structures, effect of nitrogen and oxygen heteroatoms and rational interlayer spacing of biocarbon materials. In comparison, activated biocarbon exhibits lower reversible capacity, ascribed to the formation of more solid electrolyte interphase and destruction of hierarchical structures via KOH activation. Cyclic voltammetry calculation indicates that both capacitance and diffusion are responsible for the excellent K ion storage. Graphical abstract: Image 1 Highlights: Hierarchical porous biocarbon was prepared from corn husk and used as the anode for potassium ion battery. The unactivated carbon anodes exhibit higher capacity and cycling stability than those of activated carbon anodes. Cyclic voltammetry calculation indicates that both capacitance and diffusion are responsible for the excellent K + storage.